2021
DOI: 10.1002/chem.202100355
|View full text |Cite
|
Sign up to set email alerts
|

Oxyphosphonium Enolate Equilibria in a (4+1)‐Cycloaddition Approach toward Quaternary C3‐Spirooxindole Assembly

Abstract: An efficient and convergent (4 + 1)-cycloaddition strategy toward the construction of spirooxindole benzofurans that involves the intermediacy of an isatin-derived oxyphosphonium enolate is presented. Mechanistic investiga-tions employing in situ NMR analysis of the reaction mixture revealed a correlation between phosphonium enolate structure and product distribution that was heavily influenced by the solvent and reaction temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…However, only limited approaches have been developed for highly efficient construction of dihydrobenzofuran‐fused spirooxindoles such as Friedel–Crafts alkylations of phenols with spiroepoxyoxindoles followed cyclization by the Appel reaction [6], Friedel–Crafts alkylation/cyclization of isatin‐derived propargylic alcohols with 2‐naphthols [7], cyclization of propargylic alcohols with aryne [8], Michael addition/iodization/cyclization process of 2‐hydroxynitroolefins and oxindoles [9], [4+1] cycloaddition of 3‐chlorooxindoles with ortho‐quinone methides [10], Michael addition/ring‐opening/closure cascade reaction of 3‐hydroxyoxindoles with coumarin‐3‐carboxylates [11], [4+1]cycloaddition of isatin‐derived oxyphosphonium enolates with with ortho‐quinone methides [12], cyclization reaction of 3‐cinnamyl‐3‐hydroxy‐2‐oxindoles and ortho‐quinone methides [13]. Despite the availability of methodologies to construct these spiro‐oxindoles, most of these synthetic strategies often suffer from prefunctionalized oxindole cores at C3 position, multi‐step synthesis, harsh reaction conditions, inefficiency and stoichiometric waste.…”
Section: Introductionmentioning
confidence: 99%
“…However, only limited approaches have been developed for highly efficient construction of dihydrobenzofuran‐fused spirooxindoles such as Friedel–Crafts alkylations of phenols with spiroepoxyoxindoles followed cyclization by the Appel reaction [6], Friedel–Crafts alkylation/cyclization of isatin‐derived propargylic alcohols with 2‐naphthols [7], cyclization of propargylic alcohols with aryne [8], Michael addition/iodization/cyclization process of 2‐hydroxynitroolefins and oxindoles [9], [4+1] cycloaddition of 3‐chlorooxindoles with ortho‐quinone methides [10], Michael addition/ring‐opening/closure cascade reaction of 3‐hydroxyoxindoles with coumarin‐3‐carboxylates [11], [4+1]cycloaddition of isatin‐derived oxyphosphonium enolates with with ortho‐quinone methides [12], cyclization reaction of 3‐cinnamyl‐3‐hydroxy‐2‐oxindoles and ortho‐quinone methides [13]. Despite the availability of methodologies to construct these spiro‐oxindoles, most of these synthetic strategies often suffer from prefunctionalized oxindole cores at C3 position, multi‐step synthesis, harsh reaction conditions, inefficiency and stoichiometric waste.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an assessment of different solvents revealed that relatively polar media are required (entries 7 and 8). The observed sensitivity of the reaction may reflect the fact that the distribution of the KR intermediate between the isomeric phosphonium enolate 2a and dioxaphospholene 2b forms (Scheme B) depends strongly on reaction conditions. Indeed, detailed VT-NMR studies have shown a delicate correlation between the speciation of KR intermediateswhich ultimately controls product distributionand the properties of the phosphine, solvent, and temperature …”
mentioning
confidence: 99%
“…To suppress the formation of epoxide 6 , ,, which was consistently observed as a side product during optimization, the order and rate of reagent addition was investigated. However, the yield of amino acid 8 was significantly reduced when α-keto ester 1a was added as the last component, or when either 1a or P­(NMe 2 ) 3 were added over 1 h (entries 9–11).…”
mentioning
confidence: 99%
See 2 more Smart Citations